Metformin Attenuates Cardiac Hypertrophy Via the HIF-1α/PPAR-γ Signaling Pathway in High-Fat Diet Rats - Liu, Yuansheng; Zhang, Qian; Yang, Lei; Tian, Wencong; Yang, Yinan; Xie, Yuhang; Li, Jing; Yang, Liang; Gao, Yang; Xu, Yang; Liu, Jie; Wang, Yachen; et al. (Frontiers in Pharmacology, 2022)
Coronary artery disease (CAD) and cardiac hypertrophy (CH) are two main causes of ischemic heart disease. Acute CAD may lead to left ventricular hypertrophy (LVH). Long-term and sustained CH is harmful and can gradually develop into cardiac insufficiency and heart failure. It is known that metformin (Met) can alleviate CH; however, the molecular mechanism is not fully understood. Herein, we used high-fat diet (HFD) rats and H9c2 cells to induce CH and clarify the potential mechanism of Met on CH. We found that Met treatment significantly decreased the cardiomyocyte size, reduced lactate dehydrogenase (LDH) release, and downregulated the expressions of hypertrophy markers ANP, VEGF-A, and GLUT1 either in vivo or in vitro. Meanwhile, the protein levels of HIF-1α and PPAR-γ were both decreased after Met treatment, and administrations of their agonists, deferoxamine (DFO) or rosiglitazone (Ros), markedly abolished the protective effect of Met on CH. In addition, DFO treatment upregulated the expression of PPAR-γ, whereas Ros treatment did not affect the expression of HIF-1α. In conclusion, Met attenuates CH via the HIF-1α/PPAR-γ signaling pathway.